Risk Factors of Birth Asphyxia Among Neonates Born in Public Hospitals of Tigray, Northern Ethiopia - Berhe YZ; Kebedom AG; Gebregziabher L; Assefa NE; Berhe LZ; Mohammednur SA; Wellay T; Berihu G; Welearegay AT; Mitiku M; Teka HG (Dove Medical Press, 2020)
Yodit Zewdie Berhe,1 Abel Gidey Kebedom,2 Letekirstos Gebregziabher,1 Natnael Etsay Assefa,3 Lidya Zewdie Berhe,4 Sumeya Ahmed Mohammednur,1 Tsegay Wellay,1 Gebregziabher Berihu,1 Alemtsehay Tewele Welearegay,1 Mengistu Mitiku,1 Hareya Gebremedhin Teka1 1School of Public Health, College of Health Science, Mekelle University, Tigray, Ethiopia; 2School of Medicine, College of Health Science, Mekelle University, Tigray, Ethiopia; 3Department of Midwifery, College of Medicine and Health Science, Adigrat University, Tigray, Ethiopia; 4School of Medicine, College of Health Science and Medicine, Bahir Dar University, Amhara, EthiopiaCorrespondence: Yodit Zewdie BerheSchool of Public Health, College of Health Science, Mekelle University, PO Box: 1871, Tigray, EthiopiaTel +251 910 695771Fax +251 344416681Email yoditzewdieb@gmail.comIntroduction: Birth asphyxia is defined by the World Health Organization as not initiating and maintaining default breathing at birth. Approximately 24% of neonatal deaths occurred annually worldwide due to birth asphyxia. About 3% of the 120 million neonates born each year acquire asphyxia in third world countries. Long-term survivors may experience cerebral palsy, delay in growth, vision, hearing and intellectual deficiency, epilepsy, difficulties with communication and behavior. Thus, this study aims to determine the risk factors of birth asphyxia among neonates who were delivered at public hospitals of Tigray, Ethiopia.Materials and Methods: Hospital-based unmatched case-control study design was implemented on 390 samples from January to February 2018. Data were collected by interviews using a structured questionnaire and checklist. The collected data were coded and entered using EpiData version 3.1 statistical software and transported to statistical package for social science (SPSS) version 20 software for analysis. Cross-tabulation and odds ratio with 95% confidence interval were computed. Bivariate logistic regression and multivariable logistic regression were done. Multicollinearity was checked. Goodness of fit was checked by the Hosmer–Lemeshow test.Results: A total of 260 controls and 130 cases were enrolled in the study. Multivariable logistic regression showed that Primi-parity [AOR 5.5 (CI: 2.5, 12.3)], pre-eclamcia/pregnancy-induced hypertension [AOR12.4 (CI: 4.17, 37.15)], post-term pregnancy [AOR 2.73 (CI: 1.00, 7.55)] meconium-stained liquor [AOR 29.2 (CI: 12.0, 71.1)], cord entangled [AOR 5.67 (CI: 1.66,19.3)] and non-vertex presentation [AOR 5.49 (CI: 2.20,13.7)] were found to be risk factors for perinatal birth asphyxia.Conclusion and Recommendations: Intrapartum factors and neonatal factors in the index pregnancy have an association with perinatal birth asphyxia. The research finding suggests effective antenatal care follow-up and follow-up of labor progress using partograph after labor initiation.Keywords: perinatal asphyxia, neonates, intrapartum, antepartum, Tigray